Analysis of the provision of private green open space (study at Perumnas Belimbing, Kuranji sub-district, Kuranji sub-district, Padang city) - Apriska, Putri; Wilis, Ratna (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to analyze: (1) The process of changing private green open space areas in Belimbing Perumnas (2) Provision of private green open spaces in Belimbing Perumnas. The method of research used is quantitative descriptive. The research population was 1615 in Belimbing Perumnas. Sampling used a random sampling technique with a proportion of 15%, totaling 205 respondents. Data collection techniques are observation and distributing questionnaires. The data analysis technique used is percentage. The research results showed that: (1) A total of 155 respondents experienced changes in yard area. A total of 117 homes experienced changes in the size of their private green spaces in the 1900s. The area of ​​private open space has changed from 3 m² to 24 m², and the factor causing the change in the area of ​​house yards in Perumnas Belimbing is due to the conversion of the yard into a built-up area by 44.39%, followed by flooding at 38.54% and small plots at 15.61%. (2) Provision of private green open space in Perumnas Belimbing, namely the area of ​​private green open space in Belimbing Belimbing was 803.74 m² or only 0.11% of the area of ​​Belimbing Perumnas. With the availability of ≤ 7-10 ornamental plants as much as 22.93%, the availability of 1 protective tree as much as 16.59%